Stosowanie rozumowań inferencyjnych w procesie wyprowadzania przez TK zasad i norm z przepisów konstytucyjnych - Ciżyńska, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Constitutional Tribunal, through its judgments, sometimes substantiates or completes constitutional norms and principles. These spheres of Polish constitutional court’s functioning are methods of interpretation specific to constitutional law, which is a branch of law fundamental for the state’s functioning. However, common courts substantiate abstract norms in individual cases, while the Constitutional Tribunal makes general clauses more concrete, often constituting legal principles, which not only can, but also should be a base for further concretization by the state’s organs.The aim of this publication is to show the interpreting of rules and principles by the Constitutional Tribunal through applying inferential reasoning, as well as an attempt to assess the permissibility of such an act of the Polish constitutional court.
Keywords: Constitutional Tribunal; Constitutional Court; inferential reasonings; substantiation; completion; constitutional rights and freedoms